Fabrication of gadolinium particle-based absorption gratings for neutron grating interferometry - Gustschin, Alex; Neuwirth, Tobias; Backs, A.; Schulz, Michael; Pfeiffer, F. (Review of Scientific Instruments, 2018)
The imaging performance of a neutron-based Talbot-Lau interferometer depends to a great extent on the absorption characteristics of the source and analyzer gratings. Due to its high neutron attenuation, gadolinium (Gd) is the preferred material for grating fabrication, but suffers from difficulties with deposition time, stability, uniformity, and selectivity into high aspect ratio structures. Here we present a simple alternative method of Gd deposition into grating structures based on metallic particle suspension casting and subsequent doctor-blading. Surface analysis by confocal and electron scanning microscopy shows that a nearly clear, particle free silicon interface of the grating structure over a large area could be reached. Additionally, characterization by neutron radiography confirms a high effective Gd height and homogeneity over the whole grating area. In particular, grating trenches well below 10 μm width could be successfully filled with Gd and deliver excellent absorbing performance down to the sub-2 Å wavelength range. The findings confirm that we obtained an effective binary absorption profile for the fabricated gratings which is of great benefit for grating-based neutron imaging.
CRIS-Team Scopus Importer:2023-03-08